Estudio geológico de la vía Alamor-Río Pindo de los Cantones Puyango y Paltas, provincia de Loja. - Bravo Granda, Byron Antonio (2013)
This thesis project aims to study the geological component of the pathway that connects the towns of Alamor, Vincentino, Orianga and Rio Pindo in the cantons Paltas and Puyango of the Loja province, by applying the field techniques, office techniques, and advanced techniques like the geological photo interpretation and management of geographic information systems (GIS), means by which the results will be a detailed geological information, with a lithological and structural description with previous field corroboration, likewise detailed map databases will be prepared along the road axis with a length of 500 m of both the left and right sides of the road. The main purpose of this thesis project will be to have information on the types of rocks and structures (faults, folds, discontinuities and others) and to serve as the basis of prior knowledge to decision taking in the implementing of the project "Study and definitive design at the asphalt level of the road Alamor, Vincentino, Orianga, Rio Pindo Km1-Km67.6 stretch."